2018
DOI: 10.3390/cancers10060161
|View full text |Cite
|
Sign up to set email alerts
|

KLF10 as a Tumor Suppressor Gene and Its TGF-β Signaling

Abstract: Krüppel-like factor 10 (KLF10), originally named TGF-β (Transforming growth factor beta) inducible early gene 1 (TIEG1), is a DNA-binding transcriptional regulator containing a triple C2H2 zinc finger domain. By binding to Sp1 (specificity protein 1) sites on the DNA and interactions with other regulatory transcription factors, KLF10 encourages and suppresses the expression of multiple genes in many cell types. Many studies have investigated its signaling cascade, but other than the TGF-β/Smad signaling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 101 publications
2
62
0
Order By: Relevance
“…To find out which of the expression changes in RNA‐Seq experiments are the most important causes of podocyte dysfunction, we focused our attention on transcriptional factors involved in the regulation of nephrin expression and found that KLF10 is a candidate target. There are currently a total of 27 SP/KLF family members identified in mouse or human, which include nine members of the SP subfamily (SP1–SP9) and 18 members of the KLF subfamily (KLF1–KLF18; McConnell & Yang, ; Bialkowska et al , ; Memon & Lee, ). Due to the structural similarities in the SP/KLF DNA‐binding domains at their C‐terminal regions and the diverse functional (transactivation/repression) domains at their N‐terminal regions, the SP/KLF members may have overlapping sets of target genes but display diverse influences on target gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To find out which of the expression changes in RNA‐Seq experiments are the most important causes of podocyte dysfunction, we focused our attention on transcriptional factors involved in the regulation of nephrin expression and found that KLF10 is a candidate target. There are currently a total of 27 SP/KLF family members identified in mouse or human, which include nine members of the SP subfamily (SP1–SP9) and 18 members of the KLF subfamily (KLF1–KLF18; McConnell & Yang, ; Bialkowska et al , ; Memon & Lee, ). Due to the structural similarities in the SP/KLF DNA‐binding domains at their C‐terminal regions and the diverse functional (transactivation/repression) domains at their N‐terminal regions, the SP/KLF members may have overlapping sets of target genes but display diverse influences on target gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…KLF10 was originally identified as a TGF‐β‐inducible early gene product in human osteoblast cells (Subramaniam et al , ). In addition to TGF‐β, KLF10 could be induced by bone morphogenetic proteins (BMPs), estrogen, nerve growth factor, and epidermal growth factor (EGF) depending on cell types and environmental conditions (Subramaniam et al , ; Memon & Lee, ). Although several KLF members including KLF2, KLF4, KLF6, and KLF15 in glomerular endothelial cells or podocytes have been linked to kidney diseases, all these reported KLF members serve as renal protectors (Mallipattu et al , , , ; Hayashi et al , , ; Zhong et al , , ).…”
Section: Discussionmentioning
confidence: 99%
“…Highly conserved C‐terminal structure and conservative binding site with CACCC boxes or GC‐rich motifs lead to a certain degree of overlap in the target genes that different KLFs regulate . Several KLFs have been reported to be involved in malignant diseases, which is in accordance with their fundamental role in the regulation of cell growth, proliferation, differentiation, and apoptosis. KLF2 appeared to inhibit cell proliferation by decreasing the expression of proto‐oncogene c‐myc, and mutations in KLF2 inactivated its ability to suppress NF‐κB activation .…”
Section: Discussionmentioning
confidence: 99%
“…Within the replicated DEGs, we observed a number of DEGs that mirrored our findings from our gene-set enrichment analysis. For example, KLF10 is a major effector in the TGF-β signaling pathway 20 and WNT8B's role in Wnt signaling may impact T effector cell differentiation 21 . Moreover, we observed the presence of several melanoma related antigens (MAGEA1, MAGEA3) in our validated DEGs that are known cancer testis antigens recognized by cytolytic T-cells in melanoma and are almost exclusively expressed by melanoma cells 22 .…”
mentioning
confidence: 99%
“…This suggests that on-treatment DEGs preferentially reflect immune-related changes induced by ICI treatment, consistent with our findings from our on-treatment differential pathway analysis. To illustrate the utility of our deconvolution algorithm as a mechanism for interpreting our DEGs, we use KLF10, a member of the TGF-β pathway that has both roles a tumor suppressor 20 and plays a role in inducing Th1/Th17 polarity and CD8+ memory T-cell formation 28 . Both roles may reflect plausible mechanisms of resistance to anti-PD1 therapy; however, our data shows that KLF10 is mostly derived from the non-tumor component, suggesting that the differential on-treatment response may be correlated with potentially with the Th1/Th17 polarity inducing function of KLF10 as opposed to its tumor suppressor role in mediating resistance to anti-PD1 therapy.…”
mentioning
confidence: 99%